Rethinking Food Security in International Relations: Famine, Vulnerability, and Conflict in Somalia - Mirajiah, Risalatu; Elfreda Harun, Khansa (Jurnal Sains Sosio Humaniora, 2026)
Food security has increasingly become an important issue in International Relations, particularly within non-traditional security studies. This article aims to rethink the concept of food security by examining the relationship between famine, vulnerability, and conflict in Somalia. Traditionally, understood as a humanitarian and development issue, contemporary global challenges such as armed conflict, political instability, climate change, and economic inequality demonstrate that food insecurity also constitutes a significant international security concern. Using a qualitative descriptive approach and literature-based analysis, this study explores how chronic famine in Somalia reflects the interconnectedness between food insecurity, state fragility, human vulnerability, and violent conflict. This study focuses on the 2020 and 2024 period, particularly covering the 2011 famine. To ensure the empirical reliability, the analysis relies on reports and datasets from key international institutions, including UN, FAO, WFP, IPC, the World Bank, and relevant scholarly publications. The findings reveal that famine in Somalia is not solely caused by natural factors such as drought, but is also deeply influenced by prolonged political instability, armed conflict, weak governance, and unequal access to resources. Furthermore, food insecurity contributes to social instability, displacement, humanitarian crises, and the expansion of extremist groups, thereby threatening both national and regional security. This article argues that food security must be viewed as a multidimensional security issue linked to international stability. By using Somalia as a critical empirical case, this study contributes to the broader discussion on non-traditional security and offers a deeper conceptual understanding of food security within International Relations studies.